Pengaruh Tax Avoidance, Manajemen Laba dan Capital Structure Terhadap Nilai Perusahaan - Fatin Wildania Rahmi (Yayasan Literasi Ilmiah Indonesia, 2024)
Purpose: Firm value as a function of tax evasion, earnings management, and capital structure is the intended subject of this research. Method: The research methodology employed in this study is a quantitative one, and secondary data was sourced from the company's official website and the Indonesia Stock Exchange (IDX) website. The research subjects for this study are manufacturing companies that will be listed on the IDX between 2019 and 2023. The data set included 200 samples selected using a purposive sampling technique. Finding: There is a negative relationship between business value and tax evasion, earnings management, and capital structure, according to this study's conclusions. Novelty: The novelty of this study is that researchers added time periods and research samples.